Evaluation Of Anxiety In Patients Undergoing Complete Denture Treatment At Two Tertiary Care Hospitals In Rawalpindi And Islamabad - Muhammad Amir Ghafoor Chaudhary; Misbah Khalid; Romeysah Adnan; Saba Uzair; Raza Ullah Khan; Muhammad Farooq Kamran (Journal of Rawalpindi Medical College)
Objective: The objective of the article is to assess anxiety in patients undergoing complete denture treatment.